AVENIR Thematic Brief: Women and youth - Mwongera, Caroline; Kinyua, Ivy Wambui (2022)
The Adaptation and Valorization of Entrepreneurship in Irrigated Agriculture (AVENIR) project aims to enhance the well-being and resilience of farming households in Senegal, particularly women and youth. A primary objective is to strengthen women and youth's capacity to operate profitable agribusinesses in selected climate-adaptive value chains such as horticulture, rice, and agroforestry based on baobab, cashew, and mango trees. This brief outlines how AVENIR strengthens women's engagement in climate-adapted value chains by building capacities, establishing market linkages, and organizing smallholder farmers in a way that maximizes their agency in order to leverage access to finance and market possibilities.